DEVELOPMENT OF DIGITAL COMICS BASED ON DILEMMA STORIES FOR THE TOPIC OF ELASTICITY AND HOOKE'S LAW: PENGEMBANGAN KOMIK DIGITAL BERBASIS DILEMMA STORY PADA MATERI ELASTISITAS DAN HUKUM HOOKE - Ayu Yulianawati; Hadi Nasbey; Upik Rahma Fitri (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
This research aims to develop a product in the form of dilemma story-based digital comics for elasticity and hooke's law. This comic is designed to improve students' understanding of the application of the concept of elasticity and Hooke's law in everyday life with more attractive images and designs. This research uses the R&D (Research and Development) method with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). This comic will be developed using 3D Pageflip Professional so that this comic can be accessed easily through computer and smartphone devices. This comic will be validated by media experts and material experts using a Likert scale. The final results of this comic will then be tested on students. Based on the results of the needs analysis conducted using a questionnaire through Google Forms to 29 high school students, the results showed that 75.9% (22 respondents) stated that they had difficulty in understanding elasticity and hooke's law material, 75.9% (22 respondents) stated that they liked reading comics/manga/webtoon, and 79.3% (23 respondents) stated that they were interested if comic media could be developed into physics learning media for elasticity and hooke's law material. Thus, Dilemma Story-Based Digital Comics on Elasticity and Hooke's Law are needed as learning media that can improve students' understanding.